Comparison of calculated dose between planned adaptive software and helical tomotherapy treatment planning programs - Intanin, Panatda; Chitapanarux, Imjai; Wanwilairat, Somsak; Nobnop, Wannapa (Biomedical Sciences and Clinical Medicine, 2015)
Purpose To compare between the calculated dose of planned adaptive software on MVCT images and the helical tomotherapy planning dose calculated on kVCT images. Methods The patients included in this study were 14 head and neck cancer cases treated by helical tomotherapy. All the planning doses were calculated by the planning station on kVCT data sets for PTV70, PTV59.4 and PTV54. The MVCT datasets were acquired by the helical tomotherapy system. The merged image between the kVCT and MVCT images was used for planned adaptive calculation. D95 of all PTVs, D50 of the parotid glands and D2 of the spinal cord were evaluated from a dose-volume histogram (DVH). These dosimetric parameters were compared using Pearson’s correlation. Results The average D95 (cGy/fraction) of kVCT and MVCT two-dose calculation for PTV70, PTV59.4 and PTV54 was 212.1, 179.9 and 164.9, and 215.8, 183.3 and 162.9, respectively. The average D50 (cGy/fraction) of kVCT and MVCT two-dose calculation for the right and left parotid glands was 89.6 and 91.0, and 85.9 and 87.1 cGy/fraction, respectively. The average D2 (cGy/fraction) of kVCT and MVCT two-dose calculation for the spinal cord was 96.1 and 98.0 cGy/fraction, respectively. Conclusions The comparison of dosimetric results in this study demonstrated that the MVCT calculated dose by planned adaptive software correlates with the planning dose on kVCT, and they can be substituted by each other.